Hey everyone, I realize that this is a pretty simple problem but i cant seem to wrap my brain around it. If someone could point me in the right direction i would be thankful. suppose (vector)C= (vector)A + (vector)B a) under what circumstances does [(vector)C]= [(vector)A] + [(vector)B]? ( [ ]= absolute value) b) could [(vector)C]= [(vector)A] - [(Vector)B]? if so how? if not, why not? ok. for A i was thinking the only way that could be true is if both A and B had the same sign, but im pretty sure thats wrong. For B I dont think both C=A+B and [C]=[A]- could be true, but im not sure why. If someone could guide me in the right direction i would be grateful. THANKS!